Processed line aerogravity data over the Dufek Massif, Pensacola Mountains (1997/99 season) - Jones, P.C. (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
A British Antarctic Survey Twin Otter and survey team acquired 8,300 line-km of aerogeophysics data during the Austral summer of 1998/99. Gravity and radio-echo data were acquired simultaneously with the magnetic data at a compromise constant barometric height of 2,200 m, which provides a terrain clearance of 100 m over the highest peaks. Two separate surveys were conducted; one at 5 km line spacing (tie lines at 20 km) over and stretching beyond the southern extent of the Forrestal range (main survey), and one at 2 km line spacing (tie lines at 8 km) covering the Dufek Massif (detailed survey). Ashtech Z12 dual frequency GPS receivers were used for survey navigation. Pseudorange data were supplied to a Picodas PNAV navigation interface computer, which was used to guide the pilot along the pre-planned survey lines. The actual flight path was recovered, using carrier-phase, continuous, kinematic GPS processing techniques. All pseudorange navigation data were recorded at 1 Hz on a Picodas PDAS 1000, PC-based data acquisition system. We present here the processed line aerogravity data collected using Lacoste and Romberg air-sea gravity meter S83. Data are provided as XYZ ASCII line data. : The dataset available here includes channels from raw through to filtered free air anomalies, populated where processing steps could be recovered from older databases. Basic details on survey design are presented in Ferris et al., (1998, 2003). Raw data from L&R meter #S83 includes: Channel names in brackets Spring tension (ST) meter units Cross coupling (CC) meter units Raw beam position (RB) mV Cross axis accelerometer output (XACC) mV Long Axis accelerometer output (LACC) mV Gravity processing steps were as follows: 1/ Calculate observed gravity. True spring tension (ST_real) is calculated from the posted spring tension (ST) correcting for the fact that for this survey the true spring tension approaches the posted value at 40 mGal per second. Beam velocity (Beam_vel) is derived from raw beam position (RB) assuming a centred difference approximation. Relative gravity (rec_grav) = ((ST_real+CC)*0.9966)+(Beam_velocity*k_fac), k_fac=60/2.04, meter scale value =0.9966. Still readings are in mGal (Still), and were calculated assuming a linear best fit to the drift of the airborne meter observed at base stations at Mario Zucchelli, Talos Dome, Dome C, and C3 (Jordan et al., 2007). Tie absolute gravity values for the survey (Base) were derived from land gravity measurements adjacent to the survey aircraft (Jordan et al., 2007). Airborne absolute gravity values (Abs_grav) = Rec_grav- Still + Base 2/ Corrections to derive free air anomalies (disturbances). Vertical acceleration (VaccCor) is calculated as 2nd derivative of flight altitude (Height_WGS1984) Eotvos correction (EotvosCor) follows (Harlan, 1968). Latitude correction (LatCor) = 978.03185(1+0.005278895 sin2Lat- 0.000023462 sin4Lat) (IUGG 1967). Free air correction (FaCor) = 0.3086*Height_WGS1984. NOTE subsequent free air values are defined as gravity disturbances in geodesy, as they are referred to the ellipsoid (Hackney and Featherstone, 2003). Horizontal acceleration correction (HaccCor). For this survey the approximation of (Swain, 1996) was used, assuming a damping factor of 0.707, and a platform period of 4 minutes. 3/ Free air anomaly and filtering. Free air anomaly (Free_air) = Abs_grav-VaccCor+EotvosCor+FaCor-LatCor-(0.5*HaccCor) Filtered free air anomaly (FAA_filt) used 9 km 1/2 wavelength space domain kernel filter (Holt et al., 2006). Final free air data (FAA_clip) was produced by manually masking turns, start and end of lines, and other regions of noisy data. Upward continued free air anomaly (FAA_2400m) was produced by upward continuing each line segment from the collected flight altitude to 2400 m, the highest altitude in the survey. Note no levelling has been applied to the free air gravity data. Channel description: Basic Channels Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_name Line Number e.g. LW200.1:12 Lon Longitude WGS 1984, for processing see readme Lat Latitude WGS 1984, for processing see readme x x projected meters* y y projected meters* Height_WGS1984 Aircraft altitude (meters) in WGS 1984, for processing see location data page Raw gravity Channels ST Spring Tension (meter units) CC Cross Coupling (meter units) RB Raw beam position (Mv) XACC Cross axis accelerometer (Mv) LACC Long axis accelerometer (Mv) Still Airborne meter still reading value (mGal) Base Absolute gravity reference, from land gravity (mGal) Calculation Channels St_real True Spring tension value (meter units) Beam_vel Gravity meter beam velocity (Mv/sec) Rec_grav Recalculated relative gravity (mGal) Abs_grav Calculated absolute gravity (mGal) VaccCor Vertical acceleration correction EotvosCor Eotvos correction LatCor Latitude correction FaCor Free air correction HaccCor Horizontal acceleration correction Free air Channels Free_air Un-filtered free air anomaly FAA_filt Filtered free air anomaly *Projected coordinates (x and y) are in Lambert conic conformal with two standard parallels defined as follows: Latitude of false origin: -80 Longitude of false origin: 80 Latitude of 1st standard parallel -83 Latitude of 2nd standard parallel -77 False easting 2000000 False northing 2000000 Positioning for the Dufek survey uses Ashtech Z12 dual frequency GPS recievers (Ferris et al, 2003). Positions are calculated for the phase centre of the aircraft antenna. All positions (Lat, lon and height) are referred to the WGS1984 ellipsoid. : No values are given for St_Real, Beam_vel , Abs_grav, VaccCor, EotvosCor, LatCor, FaCor, and HaccCor. This intermediate information is not available for this legacy data.